Upaya Peningkatan Kompetensi Lulusan Melalui Program Niha’ie Mahasantri Intensif di IDIA Prenduan - Musleh Wahid; Nur Farida (Journal Innovation In Education, 2023)
The Islamic education system as a whole has components that can create an ideal Muslim figure, this is because the Islamic boarding school education system is based on the Qur’an and hadits. So that, the IDIA Prenduan has also created a unique system to support graduate competencies that are expected to be useful and have the potential to solve every problem in society. The researcher formulates the problem that is the focus of the research as follows:1. What are the efforts in improving the competence of graduates through niha’ie program among female intensive students at IDIA Prenduan? 2. What are the supporting and inhibiting factors for improving the competence of graduates through niha’ie program among female intensive students at IDIA Prenduan?This research uses a qualitative approach to the field type. Meanwhile, data collection techniques use interviews, observation, documentation. The data analysis technique is in the form of interactive analysis by Miles and Huberman with stages consisting of data reduction, data presentation, and drawing conclusions. Regarding the validity of the data, researchers used triangulation techniques. From the research results, it can be seen that the efforts in improving the competence of graduates through niha’ie program among female intensive students at IDIA Prenduan are: cergam (religious speech), congregational prayer practice, amaliyah tadries, muqobalah syakhsiyah, fathul kutub. The supporting factors are the provision to maximize when involved in these activities. While the inhibiting factors include the existence of clashes between ma'had programs and faculty programs. Keywords:The Effort, The Competence of Graduates.